Challenges university students face while studying away from hometown: A cross-sectional study - Khalid E Medani; Mohammed A Alqadhibi; Abdullah M Almutairi; Rayan H A. Asiree; Mohammad A Silsilah; Khalid N Almutairi; Waqas Sami (Wolters Kluwer Medknow Publications, 2024)
This study aims to highlight the challenges that undergraduates face when traveling a significant distance from home to study. These challenges are psychological, financial, and nutritional. The study was descriptive and based on a survey conducted to investigate the challenges faced by university students while studying away from their hometown. A questionnaire was used to collect data from 214 undergraduates between February and April 2021. The collected data were analyzed using the computer program SPSS version 24. Pearson's Chi-square and Fisher's exact tests were applied to observe associations between qualitative variables. A total of 214 undergraduates participated in the study, with a median age of 22 years. The study found significant relationships between weight change and housing (P < 0.001), weight change and distance (P < 0.001), level of homesickness and housing (P < 0.001), level of homesickness and college distance (P < 0.001), and financial status with housing (P = 0.025). The study revealed that a significant number of undergraduate participants face psychological, financial, and nutritional challenges. These challenges include psychosocial issues, such as homesickness financial difficulties, such as money issues, and nutritional concerns, such as weight changes.